The Development of the Vulnerability Index (VI) using Principal Component Analysis (PCA) - Salleh, Siti Aekbal; Isa, Nurul Amirah; Siman, Nurul Aida; Zakaria, Nur Hidayah; Pintor, Lynlei L.; Yaman, Rostam; Che Dom, Nazri (International Journal of Sustainable Construction Engineering and Technology, 2023)
Climate change elevates the rate of emergence of urban heat islands (UHIs), especially in the tropics. UHIs severely affect human comfort and health. Many studies have suggested that urban areas should be properly mitigated or planned. To cope with this, it is best to present the issue using easy-to-understand approaches to allow for better decision-making, especially during urban planning. Based on the information, adaptations and mitigation strategies can be suggested in order to reduce the impact. Hence, this research was aimed at determining the heat vulnerability index (HVI) of urban areas. This study was conducted in Malaysia in the Klang Valley, a tropical city with a complex urban morphology. Remote sensing techniques were employed to extract and derive the spatial index values for exposure, sensitivity, and adaptive capacity. A principal component analysis (PCA) was used to estimate the vulnerability as well as to generate the HVI. The most vulnerable districts were found to be Petaling (1.00), Kuala Lumpur (0.99), and Putrajaya (0.95). Kuala Lumpur had a level of exposure that was high (0.56), a level of sensitivity that was high (0.84), and capacity to adapt that was low (0.54), while Petaling had a high exposure value (0.56), very high sensitivity (1), and high adaptive capacity (0.72). A Pearson’s correlation (r) test also revealed that the variables used were highly correlated. From the preliminary findings, the vulnerability of the population to high temperatures in the Klang Valley can be identified to help develop adaptative plans that are targeted as a response to rapid warming in the future in Malaysia.